2022
DOI: 10.1002/cae.22498
|View full text |Cite
|
Sign up to set email alerts
|

A co‐creation experiment for virtual laboratories of mechanics in engineering education

Abstract: Based on the background and expertise gained during almost two decades of development and implementation of virtual laboratory applications for teaching mechanics in engineering faculties, the authors propose a novel approach for this field, in which students themselves become developers of educational computer simulations. The method, called DYOVL ("Do Your Own Virtual Laboratory"), was applied, first experimentally and then on a regular basis, with gradual optimization during consecutive years, within the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In distant learning, a virtual machine can be used in some practical courses to ensure that the learning objectives are met. These machines are usually integrated into mechanical software and can be used in the classroom or online (Craifaleanu & Craifaleanu, 2022). A three-step teaching methodology for students of design and mechanical manufacturing at Nabeul's Higher Institutes of Technological Studies has been developed to enable them to carry out practical courses on coordinating measuring machines.…”
Section: Virtual Machinementioning
confidence: 99%
“…In distant learning, a virtual machine can be used in some practical courses to ensure that the learning objectives are met. These machines are usually integrated into mechanical software and can be used in the classroom or online (Craifaleanu & Craifaleanu, 2022). A three-step teaching methodology for students of design and mechanical manufacturing at Nabeul's Higher Institutes of Technological Studies has been developed to enable them to carry out practical courses on coordinating measuring machines.…”
Section: Virtual Machinementioning
confidence: 99%
“…However, as has been indicated, practical training in all the aspects involved in autonomous driving may require a significant workload in addition to expensive equipment, which is not always available. As solutions in these cases, in which classroom experimentation is complex, virtual laboratories have been used in numerous disciplines [4,32]. Technologies such as virtual reality have also been shown to be tools of great value and potential [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…This approach emphasizes student-centered instruction, peer collaboration, and inquiry-based learning. Studies have shown that active learning techniques can lead to improved learning outcomes and higher levels of student engagement and motivation [7,11,30]. Furthermore, researchers have also explored the effectiveness of different evaluation methods in mechanics teaching.…”
Section: Introductionmentioning
confidence: 99%